2004
DOI: 10.1111/j.0001-5172.2004.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane‐induced malignant hyperthermia during cardiopulmonary bypass and moderate hypothermia

Abstract: A 56-year old man was admitted for elective mitral valve repair and coronary artery bypass surgery due to mitral valve leakage and unstable angina. After induction of anaesthesia he developed a combined metabolic and respiratory acidosis. Different diagnosis were considered and we decided to treat the patient with dantrolene due to suspicion of malignant hyperthermia (MH). The patient received one dose of dantrolene 2,5 mg/kg during cardiopulmonary bypass (CPB) and a second dose of dantrolene 2,5 mg/kg during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…acceptable limits and with an added hypothermia of CPB, could have masked the frank changes of MH, though the covert underlying progress of MH was not halted, regardless. This is consistent with the reported progression of MH, despite CPB-dependent hypothermia, with another halogenated anesthetic gas, sevoflurane and that the reversal of hypothermic-CPB by itself can exacerbate metabolism and induce MH [24,32].…”
Section: Discussionsupporting
confidence: 90%
“…acceptable limits and with an added hypothermia of CPB, could have masked the frank changes of MH, though the covert underlying progress of MH was not halted, regardless. This is consistent with the reported progression of MH, despite CPB-dependent hypothermia, with another halogenated anesthetic gas, sevoflurane and that the reversal of hypothermic-CPB by itself can exacerbate metabolism and induce MH [24,32].…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study are consistent with clinical presentations of sevoflurane‐induced MH: it seems that sevoflurane utilized for general anesthesia is a less potent trigger compared with halothane. Even though numerous case reports about MH crisis after sevoflurane application have been published, the period from the first contact with sevoflurane until the onset of symptoms seems longer and clinical symptoms seem less severe compared with halothane . On a cellular level, sevoflurane increased sensitivity of sarcoplasmic calcium release by interaction with the high affinity sarcoplasmic reticulum calcium‐binding site .…”
Section: Discussionmentioning
confidence: 99%
“…While halothane lost its clinical relevance in the developed countries, and therefore, the availability of the substance became more difficult, the EMHG encouraged inquiries about possible alternatives for the IVCT. Sevoflurane is a known trigger for MH, and the trigger potency has been confirmed by numerous proven clinical MH episodes in patients after sevoflurane administration . Moreover, the substance induced MH crisis in susceptible pigs and was a suitable trigger in a minimal invasive in vivo MH testing trial .…”
mentioning
confidence: 91%
“…Jonassen et al [10] reported that MH emerged about 20 minutes after anesthetic induction with sevoflurane in a 56-year-old man who was undergoing cardiopulmonary bypass and moderate hypothermia. Cheong et al [11] reported that MH emerged about 150 minutes after general anesthesia with sevoflurane in a 24-year-old man who was undergoing bilateral sagittal split ramus osteotomy.…”
Section: Discussionmentioning
confidence: 99%